Combined exome analysis and exome depth assessment achieve a high diagnostic yield in an epilepsy case series, revealing significant genomic heterogeneity and novel mechanisms. (2nd January 2023) - Veltra, Danai; Tilemis, Faidon-Nikolaos; Marinakis, Nikolaos M.; Svingou, Maria; Mitrakos, Anastasios; Kosma, Konstantina; Tsoutsou, Irene; Makrythanasis, Periklis; Theodorou, Virginia; Katsalouli, Marina; Vorgia, Pelagia; Niotakis, Georgios; et al.
ABSTRACT: Objectives: Genetics of epilepsy are highly heterogeneous and complex. Lesions detected involve genes encoding various types of channels, transcription factors, and other proteins implicated in numerous cellular processes, such as synaptogenesis. Consequently, a wide spectrum of clinical presentations and overlapping phenotypes hinders differential diagnosis and highlights the need for molecular investigations toward delineation of underlying mechanisms and final diagnosis. Characterization of defects may also contribute valuable data on genetic landscapes and networks implicated in epileptogenesis. Methods: This study reports on genetic findings from exome sequencing (ES) data of 107 patients with variable types of seizures, with or without additional symptoms, in the context of neurodevelopmental disorders. Results: Multidisciplinary evaluation of ES, including ancillary detection of copy number variants (CNVs) with the ExomeDepth tool, supported a definite diagnosis in 59.8% of the patients, reflecting one of the highest diagnostic yields in epilepsy. Conclusion: Emerging advances of next-generation technologies and ' in silico ' analysis tools offer the possibility to simultaneously detect several types of variations. Wide assessment of variable findings, specifically those found to be novel and least expected, reflects the ever-evolving genetic landscape of seizure development, potentially beneficial for increased opportunities for trial recruitment and enrollment, and optimized, even personalized, medical management.